Gender discrimination in surgical oncology: An in-house appraisal - Pandrowala, Saneya; Patkar, Shraddha; Nair, Deepa; Maheshwari, Amita; Pramesh, C. S.; Puri, Ajay (Frontiers in Surgery, 2022)
Introduction Gender discrimination (GD) though rarely blatant, may present indirectly within a surgical department in the form of subtle inequities, differing standards, and bias. GD encompasses a wide spectrum including academic development, surgical opportunities and sexual harassment. Methods We conducted an online survey to analyse the perceived incidence of GD in the surgical oncology department at a tertiary care cancer centre in India. The questionnaire consisted of 15 questions and was mailed to the entire department including trainees and faculty. Anonymity was maintained while collecting the data only of the participants’ gender and whether they were faculty or trainee. Collated responses were analysed using proportions. Results The questionnaire was sent out to 200 recipients of whom 56% (112/200) responded via an online survey. Respondents included 84% of faculty (42/50) and 46.6% of trainees (70/150). GD was perceived by 28% of female trainees (7/25) as compared to 6.6% of male trainees (3/45), whereas amongst faculty, GD was perceived by 26.6% of female faculty (4/15) compared to 14.8% of male faculty (3/27). Approximately 13 % of our trainees and 12 % of our faculty mentioned that GD affected their professional performance or mental well-being. GD was experienced in terms of work experience and opportunities by a majority of trainees (13%) and faculty (9.5%). There was a significant lack of awareness about recourse to an institutional grievance committee by trainees (47%) compared to faculty (14%). About 7% of trainees and 12% of faculty acknowledged that they may have been responsible for intentional/unintentional GD. Conclusion Gender discrimination can present in subtle or overt fashion in surgical departments and requires active sustained efforts to allow both genders to feel equally empowered. Establishing a system to objectively evaluate gender equity while avoiding stereotyping for certain roles can help minimize GD.